PEMBELAJARAN BERBASIS PROYEK DALAM PENDIDIKANAGAMA ISLAM: DAMPAK TERHADAP KREATIVITAS DANKETERLIBATAN SISWA - Pasaribu, Sufriansyah (Tarbiyah : Jurnal Pendidikan Agama Islam, 2024)
This article examines the implementation of a Project-Based Learning (PBL) model in Islamic Religious Education (PAI) to enhance student creativity at SMP N 3 Sibolga. Employing a descriptive qualitative approach, the research involved field observations, interviews, and document analysis. Data validation was ensured through credibility tests, followed by data reduction, presentation, and conclusion drawing. The study participants included the head of the madrasa, the Deputy Head of Curriculum, PAI teachers, and 9th-grade students. The findings reveal that PBL in PAI improves students' communication, engagement, and creativity in PAI  lessons. The model involves three stages: introduction, core activity, and closure. The success of PBL is attributed to factors such as skilled teachers, motivated students, and sufficient resources. However, challenges like varying student abilities and limited time allocation were identified